The Influence of Brand Ambassadors and EWOM on Purchasing Decisions for Skincare Skintific in the Shopee Application - Riki Fernando; Hasanah Khalaidah; Rahmadi Rahmadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The development of the digital domain shows a significant increase, both internationally and domestically. This study aims to examine the influence of Brand Ambassadors and Electronic Word of Mouth (E-WOM), both separately and in conjunction, on Purchasing Decisions within the Shopee application. The research employs a quantitative methodology based on data collected through surveys. The sample consists of 120 respondents who utilize skincare products from the Shopee platform. This research utilizes conventional assumption testing instruments and multiple linear regression for data analysis. The findings indicate that both Brand Ambassadors and E-WOM have a positive and significant impact on Purchasing Decisions, both independently and collectively, within the Shopee mobile app.